TOURISM DEVELOPMENT IN THE COASTAL ISLAND ° OF GUIMARAS PHILIPPINES - Suzanna Ratih Sari (JOURNAL OF COASTAL DEVELOPMENT, 2001)
Tourism is a multi-discqalinary activitjy that touches almost every aspect of human endeavor. In view of its international character and its role in the development of the national economy, an attempt has been made to study the economic, socio-cultural and environmental impact of tourism on regional development in developing countries such as the Philippines. Tourism development is an economic and industrial activity involving many individuals, firms, corporations, organizations and associations. It is economically important as it provides a source of income and employment, brings in infra-structural improvements and helps in regional development. (Negi, 1990) For a province such as Guimaras Island tourism development is a powerful tool needed in ‘ solving sonic of the provincial problems. Furthermore, in some cases, it contributes to the national economy by developing and revitalizing the economic condition more quickhi than other industries. Many sectors ofthe community benefitjrom the injection of additional wealth that tourism brings